Effect of Early Life Stress on the Epigenetic Profiles in Depression - Li, Ming; Fu, Xiying; Xie, Wei; Guo, Wanxu; Li, Bingjin; Cui, Ranji; Yang, Wei (Frontiers in Cell and Developmental Biology, 2020)
Depression is one of the most common mental disorders and has caused an overwhelming burden on world health. Abundant studies have suggested that early life stress may grant depressive-like phenotypes in adults. Childhood adversities that occurred in the developmental period amplified stress events in adulthood. Epigenetic-environment interaction helps to explain the role of early life stress on adulthood depression. Early life stress shaped the epigenetic profiles of the HPA axis, monoamine, and neuropeptides. In the context of early adversities increasing the risk of depression, early life stress decreased the activity of the glucocorticoid receptors, halted the circulation and production of serotonin, and reduced the molecules involved in modulating the neurogenesis and neuroplasticity. Generally, DNA methylation, histone modifications, and the regulation of non-coding RNAs programmed the epigenetic profiles to react to early life stress. However, genetic precondition, subtypes of early life stress, the timing of epigenetic status evaluated, demographic characteristics in humans, and strain traits in animals favored epigenetic outcomes. More research is needed to investigate the direct evidence for how early life stress-induced epigenetic changes contribute to the vulnerability of depression.